Effect of iron on the Ni/clay catalyst for steam dealkylation of toluene. A technical note - Mayorga, José (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper studied the effect of Iron on the catalyst for steam dealkylation of toluene. Four catalysts with 5% NI/clay and quantities of iron from O to 0,6% by weight were prepared. The best results obtained by using a catalyst with 5% Ni and 0,4% Fe. These results show that iron acts as a chemical promoter of the catalyst.